Large-scale examination of hot and cool executive function in children born preterm - Iris Menu; Mark Duffy; Tanya Bhatia; Sofia Trapaga; Jenna John; Selma Music; Daelah Nicholas; Seyeon Yim; Moriah E. Thomason (Developmental Cognitive Neuroscience)
Preterm birth can significantly impact cognitive development, particularly executive functions (EF). This study investigated hot (with emotional/motivational aspects) and cool (purely neutral/cognitive) EF trajectories in preterm and full-term children, examining brain-behavior relationships. It included 3508 participants aged 9–10 years (mean age 10.0 years) at baseline from the Adolescent Brain and Cognitive Development (ABCD®) study, evenly split between preterm and full-term births (54.36 % males; 1.05 % Asian American, 10.69 % Black, 15.68 % Hispanic, 61.57 % White, 11.09 % other). Participants were followed for 4 years, completing MRI scans and a cool EF task at baseline and at the 2-year follow-up, as well as hot/cool and hot EF tasks at the 1- and 3-year follow-ups. Linear mixed models showed varying effects of preterm birth across the different EF tasks. Specifically, preterm children showed persistent cool EF deficits and a catch-up pattern for hot EF, while performance on the hot/cool task showed no association with preterm birth. Brain-behavior bivariate latent change score analyses identified distinct bidirectional relationships in specific regions, suggesting altered cognitive-brain maturation interactions in preterm children. These findings highlight the complex nature of EF development following preterm birth: while cool EF deficits persist, hot EF shows catch-up growth in preterm children during early adolescence. This emphasizes the need for tailored interventions and long-term follow-up in this population.